Non-compliance with temporary agency work regulations: Initial evidence from Germany - Angelika Ganserer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Temporary agency work and outsourcing to a service contractor are two forms of alternative work arrangements with rather complex legal aspects which firms use for external staffing. The regulatory complexity of temporary agency work can lead to intended or unintended non-compliance when firms outsource to a service contractor. In this paper, I provide first evidence for non-compliance with temporary agency work regulations when firms contract out on the basis of a unique new firm survey. By exploiting a choice experiment, I demonstrate that firms do understand the regulatory baseline of temporary agency work, although detailed knowledge often seems to be missing. Non-compliance with regulations therefore often results from ignorance of the legal grayzone.
Keywords: K31; J41; J83; M55; 330; temporary agency work; contracting out; compliance; choice experiment